2012
DOI: 10.1002/ejlt.201100333
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of fatty acid profiles in ruminant and non‐ruminant milk

Abstract: This is a comprehensive study of fatty acid (FA) profiles in milk from bovine, caprine, ovine, asine, and equine species. Milks from these species are universally common as constituents in a variety of different food and dairy products. We have obtained structural information on FAs, and discussed their correlation to health effects. The extracted fat from all species were derivatized to FA methyl esters for analysis by GC-MS. Large differences in the lipid content and FA composition between ruminants and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 32 publications
2
29
1
1
Order By: Relevance
“…However, Medhammar et al . and Devle et al . reported the concentrations of C18:1 t11 in donkey milk.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Medhammar et al . and Devle et al . reported the concentrations of C18:1 t11 in donkey milk.…”
Section: Discussionmentioning
confidence: 97%
“…Small concentrations of CLAc9t11 have been observed in horse milk but have never been detected in donkey milk . However, Medhammar et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large differences among lipid content and fatty acid composition between ruminants and nonruminants were observed by Devle et al (2012), who reported that milk from monogastric animals is characterized by high PUFA content (e.g., 19.3% and 14.2% PUFAs in milk from horses and donkeys, respectively). Our results, however, were higher than these for mature milk from tapirs.…”
Section: Discussionmentioning
confidence: 99%
“…По содержанию лактозы, например, кобылье молоко значительно превосходит молоко жвачных животных [1]. Кобылье молоко отличается низким содержанием жира по сравнению с молоком других сельскохозяйственных животных, но вместе с тем -высоким содержанием поли-ненасыщенных жирных кислот (ПНЖК): от 13 до 51% всех жирных кислот, в частности линолевой и ␣-линоленовой кислоты [2][3][4]. Эти данные позволяют рассматривать кобы-лье молоко как перспективный источник ПНЖК -эссенци-альный фактор детского питания, участвующий в развитии нервной системы, зрения, иммунитета [5][6][7].…”
Section: обоснованиеunclassified